Assessing competitiveness and complementarity in agricultural trade between China and Cambodia pre-pandemic and post-pandemic - Zhe Tao; Siva Shankar Ramasamy; Nathee Naktnasukanjn; Fangli Ying (PLoS ONE, 2025)
The concepts of trade competitiveness and complementarity function as key indicators for assessing the strengths and weaknesses of a nation’s export profile, as well as predicting future trade trajectories. Analyzing the levels of competitiveness and complementarity within the agricultural sectors of Cambodia and China is imperative for understanding and comparing their respective competitive advantages. This study utilizes quantitative research methodologies to analyze the agricultural trade dynamics between China and Cambodia before and after the pandemic. Specifically, the research involves the calculation of the revealed comparative advantage (RCA) index, the trade complementarity index (TCI), the trade intensity index (TII), and the Grubel-Lloyd (GL) index, covering the period from 2017 to 2022. The data is from the UN Commodity Trade Statistics Database through the HS code 1-24. The study used a three-year period as a short research phase and applied two phases to compare pre-pandemic and post-pandemic. The empirical results demonstrated that China and Cambodia both exhibit a strong comparative advantage in exporting specific items. From 2017 to 2019, China has comparative advantages in exporting HS items 05,13 and 16, and Cambodia has comparative advantages in exporting HS items 10,11 and 17. From 2020 to 2022, China has a comparative advantage in exporting HS item 13, and Cambodia has a comparative advantage in exporting HS item 10. Both China and Cambodia have specific complementary agricultural items in bilateral agricultural exports from 2017 to 2019, but China does not have complementary exports in its exports and Cambodia’s imports from 2020 to 2022. The trade intensity index underscores the advantages of their bilateral trade in the direction of China’s exports to Cambodia. Inter-industry advantages are identified in specific agricultural products. This study is beneficial for the Cambodian government and relevant stakeholders in formulating sustainable policies to promote agricultural trade after pandemic. The insights derived from these indices will furnish a rigorous foundation upon which the Cambodian government can develop and implement evidence-based sustainable strategies to optimize and enhance its agricultural trade performance.